2022
DOI: 10.3389/fpls.2022.869582
|View full text |Cite
|
Sign up to set email alerts
|

The Common Bean V Gene Encodes Flavonoid 3′5′ Hydroxylase: A Major Mutational Target for Flavonoid Diversity in Angiosperms

Abstract: The classic V (violet, purple) gene of common bean (Phaseolus vulgaris) functions in a complex genetic network that controls seed coat and flower color and flavonoid content. V was cloned to understand its role in the network and the evolution of its orthologs in the Viridiplantae. V mapped genetically to a narrow interval on chromosome Pv06. A candidate gene was selected based on flavonoid analysis and confirmed by recombinational mapping. Protein and domain modeling determined V encodes flavonoid 3′5′ hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…The most significant SNP for seed coat color in tepary bean is SNP S06_11037669 which was statistically significant for L* and b* . This SNP was located 56 kbp from tepary gene Phacu.CVR.006G029800, which is a homolog of the recently characterized Flavonoid 3′5' Hydroxylase (F3′5′H) gene (Phvul.006G018800) (McClean et al., 2022) at the classical V locus. The master regulator of seed coat color in common bean is the P gene which is located on chromosome Pv07 (McClean et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The most significant SNP for seed coat color in tepary bean is SNP S06_11037669 which was statistically significant for L* and b* . This SNP was located 56 kbp from tepary gene Phacu.CVR.006G029800, which is a homolog of the recently characterized Flavonoid 3′5' Hydroxylase (F3′5′H) gene (Phvul.006G018800) (McClean et al., 2022) at the classical V locus. The master regulator of seed coat color in common bean is the P gene which is located on chromosome Pv07 (McClean et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The gene Phvul.006G018800 located in this region encodes a F3’,5’H and was previously proposed as the gene controlling the black seed coat color in the cultivar TU [ 26 ]. Later, McClean et al [ 27 ] confirmed that V encodes an F3’,5’H required for the expression of dihydromyricetin-derived metabolites. Beninger et al [ 6 , 24 ] affirmed that anthocyanin production is dependent on the V gene, since the presence of dominant genotypes V leads to anthocyanin accumulation, whereas recessive genotypes v results in flavonol accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the P gene was confirmed to be a basic helix-loop-helix ( bHLH ) MYB transcription factor, with two candidate genes, Phvul.007G171333 and Phvul.007G 171466, that allows or blocks the expression of other color genes [ 21 ]. García-Fernandez et al [ 26 ] using a RIL population derived from the cross TUxMUSICA identified two candidate genes controlling black seed coat color, Phvul.006G018800 encoding an F3´5´H on Pv06 that correspond to V color gene [ 27 ], and Phvul.008G038400 encoding a MyB113 transcription factor on Pv08 that could correspond to the C color locus.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of recessive zz donors lines V0869 (PI527806), V0919 (PI527820), and Earliwax (PI549618) used to develop multiple introgression lines, was extracted from a 40X resequencing data set (McClean et al 2022). Relative to 5-593, all three lines share the 12 nt in-frame deletion with G19833.…”
Section: Resultsmentioning
confidence: 99%